How neuropsychology can inform our understanding of preschool ADHD: Clinical and research implications. Issue 2 (3rd April 2019) - Aretouli, Eleni
ABSTRACT: Neuropsychological assessments in preschoolers have not received as much attention as in older children and adults. Attention-deficit/hyperactivity disorder (ADHD) is a common disorder that occurs in early childhood associated with poor academic and personal outcomes, such as learning and social difficulties. Preschoolers with ADHD may present cognitive deficits that are related with the ADHD symptoms of inattention, hyperactivity, and impulsivity, but may also interfere, beyond and above the ADHD symptoms, with everyday functioning. Most importantly, cognitive deficits in preschoolers seem to predict future ADHD symptoms. Yet, the practice of neuropsychological assessment in this age-group has been limited. The present selective review highlights the contribution of comprehensive neuropsychological assessments to the early identification of symptomatic preschoolers and to our understanding of the nature and developmental trajectory of ADHD.